2012
DOI: 10.1136/bmjopen-2012-001829
|View full text |Cite
|
Sign up to set email alerts
|

HIV incidence among men who have sex with men in Beijing: a prospective cohort study

Abstract: Objectives(1) To assess the HIV incidence rate among men who have sex with men (MSM) in a large cohort study in Beijing, China and (2) to identify sociodemographic and behavioural risk factors of HIV seroconversion among MSM in Beijing, China.DesignA prospective cohort study.SettingBaseline and follow-up visits were conducted among MSM in Beijing, China.ParticipantsA cohort of 797 HIV-seronegative MSM was recruited from August to December 2009, with follow-up occurring after 6 and 12 months.Primary and seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
5
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 19 publications
2
36
5
4
Order By: Relevance
“…The prevalence of syphilis (29.62%) was higher than in previous studies conducted among MSM in Beijing, which found a prevalence of 19.8% in 200724 and 22.0% in 2009 10. The incidence of syphilis (11.11/100 PY) was also extremely high compared to the rate of 8.06/100 PY reported in a cohort study among MSM during the same period in 2009 25. A high prevalence of syphilis among MSM is a common risk factor for HIV infection because of the biological and behavioural links between syphilis and HIV 28…”
Section: Discussioncontrasting
confidence: 63%
“…The prevalence of syphilis (29.62%) was higher than in previous studies conducted among MSM in Beijing, which found a prevalence of 19.8% in 200724 and 22.0% in 2009 10. The incidence of syphilis (11.11/100 PY) was also extremely high compared to the rate of 8.06/100 PY reported in a cohort study among MSM during the same period in 2009 25. A high prevalence of syphilis among MSM is a common risk factor for HIV infection because of the biological and behavioural links between syphilis and HIV 28…”
Section: Discussioncontrasting
confidence: 63%
“…The possible explanation was that younger MSM were more likely to worry about the long term side effects of TDF. However, younger MSM are at higher risk of HIV infection compared to the older MSM (17,18) and playing an important role in the transmission of HIV in China (18,19). In addition, we found that nonlocal residents were more willing to use TDF for HIV prevention than local residents.…”
Section: Discussionsupporting
confidence: 48%
“…HSV-2 incidence in our sample was lower than that recently reported among HIV-1-discordant couples in Kenya (14.8 per 100 PY) 9. There are limited data available on HSV-2 incidence in China, mostly coming from female sex workers and men who have sex with men, with an estimated incidence of 21.9 per 100 PY and 8.1 per 100 PY, respectively 20 21. The relatively low overall incidence in our sample may be attributed to the lower proportion of participants with an initially HSV-2 seropositive partner, as well as the higher rates of condom use with study partner and relatively lower prevalence of high-risk sexual behaviour.…”
Section: Discussioncontrasting
confidence: 77%